Outward investment by Trans-Latin enterprises: reasons for optimism - Michael Mortimore; Carlos Razo (Columbia University, Vale Columbia Center on Sustainable International Investment (VCC), 2009)
Despite the global crisis, outward FDI by Latin American firms grew by more than 40% in 2008. The picture for 2009 is less clear, due to the expected regional GDP contraction, falling commodity prices, and tightening credit markets. Nonetheless, the authors argue that many countervailing factors make Latin American investment more resilient in the crisis than other regions may be.
Keywords: 330